2015
DOI: 10.1097/sla.0000000000001456
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Bundle Checklist Combined With Physician Confirmation Reduces Risk of Nosocomial Complications and Death in Trauma Patients Compared to Documented Checklist Use Alone

Abstract: Bedside confirmation of bundle checklists during physician extender rounds reduces the risk of pulmonary embolus, pneumonia, and death when compared to chart documentation alone. This study underscores the importance of the team approach to the bundle checklist and it's ability to reduce morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In the bedside ward rounds of critical patients, the checklist can be used to quickly identify the the focus of quality inspection [ 8 ]. Nine cohort studies [ 8 , 10 , 14 , 16 , 18 ] and two RCTs [ 15 , 17 ] were included in this study, and the results showed that the application of the bedside ward round checklist could reduce the incidence of unexpected adverse events in critical patients and play a positive role in improving the prognosis of critical patients, of which 2 cohort studies [ 11 , 13 ] revealed that the application of the bedside ward round checklist can reduce the incidence of DVT in critical patients, 1 RCT [ 16 ] and 5 cohort studies [ 8 , 9 , 11 , 16 , 17 ] showed that the bedside ward round checklist is conducive to reducing ICU hospitalization time, and 5 clinical studies [ 1 , 2 , 8 , 10 , 11 ]showed that ICU critically ill patients need to be treated with mechanical ventilation. Due to long-term hospitalization in ICU, the risk of infection will increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the bedside ward rounds of critical patients, the checklist can be used to quickly identify the the focus of quality inspection [ 8 ]. Nine cohort studies [ 8 , 10 , 14 , 16 , 18 ] and two RCTs [ 15 , 17 ] were included in this study, and the results showed that the application of the bedside ward round checklist could reduce the incidence of unexpected adverse events in critical patients and play a positive role in improving the prognosis of critical patients, of which 2 cohort studies [ 11 , 13 ] revealed that the application of the bedside ward round checklist can reduce the incidence of DVT in critical patients, 1 RCT [ 16 ] and 5 cohort studies [ 8 , 9 , 11 , 16 , 17 ] showed that the bedside ward round checklist is conducive to reducing ICU hospitalization time, and 5 clinical studies [ 1 , 2 , 8 , 10 , 11 ]showed that ICU critically ill patients need to be treated with mechanical ventilation. Due to long-term hospitalization in ICU, the risk of infection will increase.…”
Section: Discussionmentioning
confidence: 99%
“…critical patients, of which 2 cohort studies [11,13] revealed that the application of the bedside ward round checklist can reduce the incidence of DVT in critical patients, 1 RCT [16] and 5 cohort studies [8,9,11,16,17] showed that the bedside ward round checklist is conducive to reducing ICU hospitalization time, and clinical studies [1,2,8,10,11]showed that ICU critically ill patients need to be treated with mechanical ventilation. Due to long-term hospitalization in ICU, the risk of infection will increase.…”
Section: Total Eventsmentioning
confidence: 99%
“…• Mortality (n = 14, 16 %) (Barcellos and Chatkin, 2020;Barnes-Daly et al, 2017;Chen et al, 2021a;Collinsworth et al, 2020;De Bie et al, 2021;Lemkin et al, 2020;Liu et al, 2016;Loberg et al, 2022;Nahouraii et al, 2019;Pun et al, 2019;Reiff et al, 2015;Verholen et al, 2021;Wilson et al, 2009;Cavalcanti et al, 2016), • Health care acquired infection (n = 9, 10 %) (Chua et al, 2010 De Bie et al, 2021;Heim et al, 2019;Hsieh et al, 2019;Loberg et al, 2022;Nahouraii et al, 2019;Pun et al, 2019;Sutton et al, 2021;Weiss et al, 2011;Wilson et al, 2009), • Delirium occurrence and duration (n = 8, 9 % n = 10, 11 %) ( Barnes-Daly et al, 2017;Boehm et al, 2020;Jablonski et al, 2017;Kamdar et al, 2013;Lee et al, 2020;Ma et al, 2021;Pun et al, 2019;Smith and Grami, 2016;Sutton et al, 2021;Tonna et al, 2021).…”
Section: Primary or Main Outcomes And Measuresmentioning
confidence: 99%
“…Hospital systems have attempted to address these issues by applying standardised approaches to patient care. Bedside checklists have been used to achieve these goals and can encourage changes in patient management including, early removal of invasive devices, and the more appropriate ordering of diagnostic tests 1–3. Checklists can also improve nurse and physician understanding of the patient care plans,4 and their use has been accompanied by shorter lengths of hospital stay 4 5.…”
Section: Introductionmentioning
confidence: 99%